Association of Psoriasis Severity with Serum Prolactin, Thyroid Hormones, and Cortisol before and after Treatment - Reza M. Robati; Parviz Toossi; Mohammad Rahmati-Roodsari; Sara Khalilazar; Ehsan Abolhasani; Nastaran Namazi; Shima Younespour (The Scientific World Journal)
Background. Prolactin (PRL) level is proposed to be associated with the severity of psoriasis although the previous studies reported different results. Objective. To find the association between PRL levels and severity of psoriasis before and after treatment. In addition, we aimed to find a difference in prolactin, thyroid stimulating hormone (TSH), thyroid hormones (T3 and T4), and cortisol levels between patients with psoriasis and normal controls. Methods. First, the levels of hormones were measured in 30 patients with psoriasis and 30 matched controls. The severity was assessed by psoriasis area and severity index (PASI). Then, patients were treated, and PASI was assessed every week until achieving PASI-75 response. At this time, the hormones were measured again and compared to the baseline. Results. No statistical significant difference was observed in the mean PRL, T3, T4, TSH, and cortisol levels between cases and controls. Comparing to the baseline, a significant decrease in PRL levels and a significant increase in T3 and serum cortisol levels were observed after treatment (P<0.05), while the changes in other hormones were not significant. Conclusion. After treatment, PRL significantly decreased, and T3 and cortisol levels significantly increased. No correlation between hormone levels and improvement of PASI score existed.